Kinetic drying of cupuaçu pulp (Theobroma grandiflorum) pre-dehydrated by immersion-impregnation - Perez, Luty Gomezcaceres; Oliveira, Francisca Marta Nascimento de; Andrade, Jerusa Souza; Filho, Mario Moreira (Revista Ciencia Agronomica, 2013)
The osmotic dehydration is an important unitary operation to transform the perishable fruits in new products with added value and longer shelf life. The application of reliable mathematical models allows prediction the behavior of various phenomena that occur during the drying process, which implies in reduction of operating cost. The cupuaçu pulp is commonly used to prepare juices and ice creams, but during the crop it is produced in large quantity, which is often discarded because of the cost of production is higher than the selling price. The aim of this study was to investigate the effect of binary and ternary solutions at the rate of convective drying and evaluate the adequacy of mathematical models to describe the drying curves of the cupuaçu. In the experiment, osmotic dehydration was carried out with binary (sucrose at 40°Brix) and ternary (80% sucrose/20% sodium chloride) solutions for three hours at room temperature, followed by conventional drying in an oven (air-circulating) at 65°C to constant weight. The experimental data were adjusted using the models of Page and Midilli, Kucuk and Yapar. The binary solution used during predrying, reduced the time of the subsequent conventional drying. Varying from 99.64 to 99.77% in the coefficient of determination (R2), the Page model showed a better adjustment to experimental data.
Cinética de secagem da polpa cupuaçu (Theobroma grandiflorum) pré desidratada por imersão-impregnação
Keywords: Theobroma; Theobroma Grandiflorum